USING “PICTURE AND PICTURE” LEARNING MODEL TO IMPROVE STUDENTS’ VOCABULARY AND ABILITY IN WRITING NARRATIVE TEXT AT SMKN 3 BANJARBARU - Runiaty, Any (Journal Compound: Improving the Quality of English Education, 2021)
This study was based on the students’ difficulties in writing a narrative text in the form of poor understanding of what a narrative text was and lack of vocabulary. This study, which was conducted at SMKN 3 Banjarbaru, was carried out using a Classroom Action Research design. This study proved the action hypotheses through two cycles. In the matter of the implementation of ‘Picture and Picture’ learning model in the study, the students had the improvement from cycle 1 to cycle 2 in being more active in the learning process, more confident to do the presentation and communication in the group discussion, and having more motivation in the learning process. The teacher also experienced an improvement in the skill of using media and teaching skills in the class. The significant improvement of students’ achievement in vocabulary and ability in writing narrative text could be seen from the increasing average score for vocabulary achievement from Cycle 1 to Cycle 2 which was from 61.42 to 69.76 and for writing achievement which was 68.57 to 69.91. The successful implementation of the use of the learning model was proven from the classical success of the students in gaining more than 75% of the students who were able to reach the KKM of 70, that was 76% of the students of X KK were able to reach the KKM 70 in Cycle 2. This result of the study showed that the implementation of the use of the ‘Picture and Picture’ learning model is very appropriate and effective to improve the students’ vocabulary and ability in writing narrative text.